2018
DOI: 10.1177/0972150918795354
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mediating Role of Employee Attitudes in the Relationship between High-Performance Work Systems and Turnover Intention among IT Professionals in India: A Serial Mediation Approach

Abstract: The primary purpose of this study was to seek an answer to the question of ‘how’ do high-performance work systems (HPWSs) relate to turnover intention (TI) among information technology (IT) professionals in the Indian IT sector. Against the backdrop of this purpose, we examined, by using multiple regression analysis and a serial mediation approach, the intervening effects that the constructs of work engagement (WE) and organizational commitment (OC) exercised, sequentially, on the relationship between HPWS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 107 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…These findings are in-line with the evidence from previous studies that were conducted in the healthcare contexts of different countries that revealed the positive effect of HPWS on WE (Ang et al ., 2013; Kloutsiniotis and Mihail, 2017; Mihail and Kloutsiniotis, 2016a), HPWS on JS (Chuang et al ., 2012; Ang et al ., 2013; Kloutsiniotis and Mihail, 2017) and HPWS on AC (Ang et al ., 2013; Mihail and Kloutsiniotis, 2016a; Kloutsiniotis and Mihail, 2017). These findings are also in-line with the HPWS studies that examined similar relationships in different industrial settings in the Indian context (Singh et al ., 2016; Ananthram et al ., 2018; Ramaprasad et al ., 2021). Therefore, as opined by Cropanzano and Mitchell (2005) regarding SET, the persons who have high exchange orientations are more likely to reciprocate with a good return than the persons with less exchange orientations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in-line with the evidence from previous studies that were conducted in the healthcare contexts of different countries that revealed the positive effect of HPWS on WE (Ang et al ., 2013; Kloutsiniotis and Mihail, 2017; Mihail and Kloutsiniotis, 2016a), HPWS on JS (Chuang et al ., 2012; Ang et al ., 2013; Kloutsiniotis and Mihail, 2017) and HPWS on AC (Ang et al ., 2013; Mihail and Kloutsiniotis, 2016a; Kloutsiniotis and Mihail, 2017). These findings are also in-line with the HPWS studies that examined similar relationships in different industrial settings in the Indian context (Singh et al ., 2016; Ananthram et al ., 2018; Ramaprasad et al ., 2021). Therefore, as opined by Cropanzano and Mitchell (2005) regarding SET, the persons who have high exchange orientations are more likely to reciprocate with a good return than the persons with less exchange orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Later, researchers examined employee perceptions and experiences of HPWS as the perceptions of employees will have a direct impact on subsequent employee attitudes and behaviours (Kehoe and Wright, 2013). Highlighting the context specificity, HPWS research in the Indian context was conducted in various industrial settings such as banking (Muduli et al, 2016), IT/ITES (Singh et al, 2016;Kataria et al, 2019;Ramaprasad et al, 2021), Hospitality (Dhar, 2015;Jaiswal and Tyagi, 2020), Telecom Rani, 2017, 2019), Healthcare (Thirupathi et al, 2023), Insurance (Garg and Punia, 2017;Garg et al, 2019); Power/electrical (Muduli and McLean, 2021) and Education (Jyoti et al, 2015). Flores et al (2016) opined that the mainstream HRM research studied positive employee attitudes because of the priority and importance of managers' agenda (organizational performance) only but not because to truly understand the HPWS impact on employees.…”
Section: Introductionmentioning
confidence: 99%
“…Employees of Indian IT organizations are young (mean age ranges between 20 and 30 years), well qualified (mostly graduates and postgraduates), largely male and have a mean tenure of 3–5 years with their organizations (e.g. Ugargol and Patrick, 2018; Ramaprasad et al ., 2021). The demographic distribution of employees in our sample was similar to the demographic distribution of employees in the Indian IT industry.…”
Section: Methodsmentioning
confidence: 99%
“…This may align better with the multifaceted nature of HPHRP (Liang et al, 2012). Third, although previous studies have reported that HPHRP can reduce employees' TI through OC (Ramaprasad et al, 2021;Valé au et al, 2021), it remains unclear whether a moderating variable exists in this relationship.…”
Section: Introductionmentioning
confidence: 92%